2007
DOI: 10.1007/s10916-007-9066-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Physical Environment on the Stress Levels of Hemodialysis Nurses in Ankara Turkey

Abstract: This study has been planned and executed as a field study for identifying the effect of physical environment on the stress levels of hemodialysis nurses who work in the official and private hemodialysis centers in the capital city of Turkey, Ankara (n=161). According to the results obtained from the study, it has been seen that "education level" and "institution of employment" of the hemodialysis nurses are significantly related with the stress levels of the hemodialysis nurses. Nurses' age, marital status, nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 13 publications
0
12
1
Order By: Relevance
“…The students may face stressors like social, environmental, academic, emotional, personal, and family. These stressors might disturb the learning ability and academic "performance of the students [4]. The most often reported stressors were failure and uncertainty related to performance and expectations for clinical practice [5].…”
Section: Introductionmentioning
confidence: 99%
“…The students may face stressors like social, environmental, academic, emotional, personal, and family. These stressors might disturb the learning ability and academic "performance of the students [4]. The most often reported stressors were failure and uncertainty related to performance and expectations for clinical practice [5].…”
Section: Introductionmentioning
confidence: 99%
“…45 More specifically in the case of working time, a study pointed to a higher risk for the younger and with less work time, 36 while another identified as the highest risk group the professionals that were older, and who had worked longer in nephrology 43 , and a third pointed to an intermediate work time, from six to ten years, as the main risk factor. 42 What can be achieved from the risks reported by the articles is that the issues of the work environment are closer to most of them, nevertheless they are varied among them, mentioning the responsibility of the institution, 46,42 to the employer's conduct with the nurse , 43 different forms of work organization 39 and the workplace and hospital institutions as a higher risk. 36,47 Other risk factors are job dissatisfaction 34 and with work environment, ergonomics and division of labor, 45 employment relationship 44 to have to jump and dislocating nurses and equipment to attend outside the sector.…”
Section: Discussionmentioning
confidence: 99%
“…46,35,45,48 The opposition in the conclusions of the articles follows the same tendency of multiplicity of results that is perceived in the risk and protection factors. The division between those who concluded that the nursing team in nephrology suffers from high levels of stress and/or burnout 46,41,44,42,37 and those that have resulted in low levels, when compared with other populations of nurses or with the normative standard, 47,43,39,45,48 is only three articles pointing to stress and burnout. This division reveals only the contradiction present in the comparison of the results of all articles, while Dolan, Strold and Hamerick, 48 in Australia, have the objective of finding support for the predetermined assertion that nurses in nephrology have good coping of the occupational stressors, Flynn, Thomas-Hawkins, and Clarke 37 bring alarming results, where one-third of the US nephrology nurses had burnout.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Work-related stress occurs when the physical or psychological demands exceed the ability of employees to control their workload [23, 24]. Nursing is a stressful profession not only because it is a demanding one, but also because nurses are exposed to numerous social, physical, and environmental stressors [25]. The sources of these stressors have been identified as follows: low job control and excessive job demands [26], low control over decisions [27], and the negative leadership style of supervisors [28, 29].…”
Section: Discussionmentioning
confidence: 99%